(untitled) (Journal of Environmental Science and Natural Resources, 2017)
Dhaka was established as a provincial capital of the Mughal ruler on the north-eastern bank of the Buriganga River during 1608-10. This river has enormous significance to the residents of Dhaka. Not only it surrounds the city, but also it provides important services to the residents including water supply, navigation, recreation, sanitation, fish production, tourism, biodiversity and flood control. A study was carried out to observe the ecological health hazards and their risk to human health of the Buriganga River. The samples were analyzed to determine water quality. The study showed that the water is high in biological oxygen demand (BOD), chemical oxygen demand (COD), Electrical conductivity (EC), Total dissolved solid (TDS), Salinity, Alkalinity, Turbidity and low in dissolved oxygen (DO) which revealed huge environmental health risks and possible ecological disruption of this river. J. Environ. Sci. & Natural Resources, 10(1): 75-80 2017